2020
DOI: 10.1021/acs.inorgchem.0c01056
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic PdCu Nanoparticles for Electrocatalysis: Multiphase or Homogeneous Alloy?

Abstract: Crystal phase structure of bimetallic alloy is an important factor determining the electrocatalytic activity toward oxidation of energy molecules. In this paper, PdCu bimetallic NPs with similar element composition and different crystal phase structural features have been synthesized hydrothermally by adjusting the content of ethylenediaminetetraacetic acid disodium salt (EDTA-2Na). Multiphase PdCu NPs composed of pure Pd and alloy phase are obtained with a low concentration (even as low as zero) of EDTA-2Na i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
(100 reference statements)
1
3
0
Order By: Relevance
“…In contrast, the binding energy of Cu 2+ 2p in Pd 0.25 Cu 0.75 /Al 2 O 3 -0.4 is negatively shifted compared to that of standard CuO. These results might be attributed to the electron transfer from Cu atoms to Pd atoms in Pd 0.25 Cu 0.75 /Al 2 O 3 –0.4, which is consistent with those reported in the literature. ,, …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, the binding energy of Cu 2+ 2p in Pd 0.25 Cu 0.75 /Al 2 O 3 -0.4 is negatively shifted compared to that of standard CuO. These results might be attributed to the electron transfer from Cu atoms to Pd atoms in Pd 0.25 Cu 0.75 /Al 2 O 3 –0.4, which is consistent with those reported in the literature. ,, …”
Section: Resultssupporting
confidence: 90%
“…These results might be attributed to the electron transfer from Cu atoms to Pd atoms in Pd 0.25 Cu 0.75 /Al 2 O 3 −0.4, which is consistent with those reported in the literature. [50][51][52][53]68,69 In short, the results of XRD, TEM, and XPS analyses collectively demonstrated that Pd and Cu species are loaded on mesoporous Al 2 O 3 as PdO and CuO, and the high activity of the catalyst is due to its unique mesoporous structure and the electron transfer between Cu and Pd.…”
Section: Methodsmentioning
confidence: 96%
“…While Pt and Pd-based catalysts offer high catalytic activities towards the required oxidation reactions, [25,26] Pd alloys with Cu exhibit an enhanced activity and increased poisoning tolerance over Pt in alkaline media. [27][28][29][30][31] However, inhomogeneity, [30,32] high synthesis temperatures, [29] and controlled composition [29] still pose challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The metals, such as Au, , Ag, Pd, , and Zn, , with high selectivity of CO 2 RR to CO, have been selected for modifying Cu-based catalysts. Among them, Pd plays a key role in the improvement of CO generation on Cu-based catalysts because Pd can form a saturated Pd–H phase at near-zero potential, where CO 2 is more easily adsorbed on Pd–H, , and control the d-band center of the active site and generate the key reduction intermediate, *COOH, thereby realizing the selective production of CO from CO 2 RR. However, the PdCu alloy catalyst still has competitive reactions in CO 2 RR, such as the competition between the product formic acid and CO after the formation of the *COOH intermediate, the hydrogen evolution reaction and CO evolution in the same potential range, and so on. , Therefore, it is necessary to improve the structure of PdCu alloys to reduce the effect of competing reactions on the production of CO from CO 2 .…”
Section: Introductionmentioning
confidence: 99%